Slapyvardžiai ir jų aiškinimas - Zaveckienė, Žiedūnė (Knygotyra, 1998)
The article deals with the main problems of research into the usage of pseudonyms. The usage of pseudonyms is a unique phenomena that occurs in different nations for various purposes (maintaining incognito, representation of a divine nature of art, possibility to publish works of banned authors, etc.) in every historical period. There are many different types of pseudonyms and every one is described in the article.The author compares the research done in this field in different countries, reveals the complexity of pseudonym retrieval and revealing. This work is a part of literary and bibliographic research and has become very intensive from the seventeenth century. The first research of pseudonyms was carried out in Germany, France and England. The work started in Russia at the beginning of nineteenth century, and in Lithuania at the end of it. Vaclovas Biržiška was one of the main researchers of pseudonyms’ usage in Lithuania.At present the main centre that is doing major work collecting Lithuanian pseudonyms, registering and revealing the persons who used them is the Centre of Bibliography and Book Science of the National M. Mažvydas Library. It has created a computerized database of Lithuanian pseudonyms. It gives a possibility to join the international programmes and pseudonyms’ databases as well as to develop a network of pseudonym registration in Lithuania. This database was used for publishing a dictionary of „Lithuanian Pseudonyms“. Almost 11 000 pseudonyms are characterized and revealed in the first two volumes of the dictionary. However, the process of discovering pseudonyms is a complex and difficult work. The revealing of a pseudonym publicly is possible only if the author gives his official permission. The revealing process requires much time. On the other hand, after some time it is not always possible to establish the author of a certain pseudonym and mistakes occur. The research of pseudonyms is one of the most intriguing fields.